PRINCIPLES TO RELY ON WHEN INDEPENDENT EDUCATION OF FUTURE TEACHERS IS ORGANIZED USING WEB-QUEST EDUCATIONAL TECHNOLOGY - Tileubayevna, Auezova Raya (Confrencea, 2023)
This article outlines the principles on which independent education of prospective teachers is relied upon when a web quest is organized using educational technology